2017
DOI: 10.2166/wcc.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal rainfall trends in the twentieth century for Bundelkhand region, India

Abstract: Globally, climate change and extreme weather events are occurring more frequently, impacting water resources and farming systems. Therefore, spatio-temporal analysis of long-term rainfall is much needed to understand the variability of rainfall occurrence. The present study attempts to analyse spatio-temporal rainfall change scenarios in the 20th century (1901–2000) over Bundelkhand, one of the drought hit regions of India. Analysis shows that major rainfall contributed from 3 months, i.e. July, August and Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…While in monsoon and pre-monsoon season, a positive trend is observed for all time scales of SPI except SPI 6 for pre-monsoon in all the 7 districts. A similar result was also found by Jana, et al [60], in which they reported a positive trend of rainfall over the northern part of Bundelkhand (i.e., Bundelkhand-UP) though the time period was different. Overall, no significant trend was found at annual, and other inter-seasonal scales (pre-monsoon, monsoon, and winter).…”
Section: Drought Trend Analysis: Mann-kendall Testsupporting
confidence: 87%
“…While in monsoon and pre-monsoon season, a positive trend is observed for all time scales of SPI except SPI 6 for pre-monsoon in all the 7 districts. A similar result was also found by Jana, et al [60], in which they reported a positive trend of rainfall over the northern part of Bundelkhand (i.e., Bundelkhand-UP) though the time period was different. Overall, no significant trend was found at annual, and other inter-seasonal scales (pre-monsoon, monsoon, and winter).…”
Section: Drought Trend Analysis: Mann-kendall Testsupporting
confidence: 87%
“…Mann Kendall (Z) values, Significance (α) and Sen's slope (Q) values over Bundelkhand region from 1981 to 2020 direction of drier time with more erratic rainfall behaviour. A declining annual rainfall trend was also observed in the studies conducted byRai et al, (2012),Thomas et al, (2014) Deo et al, (2015),Jain et al ,(2017) andAhmed et al, (2019) which comply with the current findings of the studies.The decreasing trend of rainfall can be due toChaurasia et al, (2021) reported that the deviation in rainfall correlates with forest cover. Thus increasing forest cover which is far below the average recommended by Nation's Forest Policy can be one of the solution to reduce water woes in the region.…”
supporting
confidence: 90%
“…The Mann-Kendall (MK) test is a nonparametric test, it was used because it does not require the data to be normally distributed, and is not very sensitive to missing data values [35]. The test has been used to detect both trends and shifts in climate and hydrological time-series datasets [36,37]. The test statistic, S, is based on the null hypothesis that there is no trend or serial correlation in a set of observations.…”
Section: Discussionmentioning
confidence: 99%